Quinolinate as a Marker for Kynurenine Metabolite Formation and the Unresolved Question of NAD+ Synthesis During Inflammation and Infection - Moffett, John R.; Arun, Peethambaran; Puthillathu, Narayanan; Vengilote, Ranjini; Ives, John A.; Badawy, Abdulla A-B; Namboodiri, Aryan M. (Frontiers in Immunology, 2020)
Quinolinate (Quin) is a classic example of a biochemical double-edged sword, acting as both essential metabolite and potent neurotoxin. Quin is an important metabolite in the kynurenine pathway of tryptophan catabolism leading to the de novo synthesis of nicotinamide adenine dinucleotide (NAD+). As a precursor for NAD+, Quin can direct a portion of tryptophan catabolism toward replenishing cellular NAD+ levels in response to inflammation and infection. Intracellular Quin levels increase dramatically in response to immune stimulation (e.g., lipopolysaccharide; LPS or pokeweed mitogen; PWM) in macrophages, microglia, dendritic cells and other cells of the immune system. NAD+ serves numerous functions including energy production, the poly ADP ribose polymerization (PARP) reaction involved in DNA repair and the activity of various enzymes such as the NAD+-dependent deacetylases known as sirtuins. We used highly specific antibodies to protein-coupled Quin to delineate cells that accumulate Quin as a key aspect of the response to immune stimulation and infection. Here we describe Quin staining in the brain, spleen and liver after LPS administration to the brain or systemic PWM administration. Quin expression was strong in immune cells in the periphery after both treatments, whereas very limited Quin expression was observed in the brain even after direct LPS injection. Immunoreactive cells exhibited diverse morphology ranging from foam-cells to cells with membrane extensions related to cell motility. We also examined protein expression changes in the spleen after kynurenine administration. Acute (8 hr) and chronic (48 hr) kynurenine administration led to significant changes in protein expression in the spleen, including multiple changes involved with cytoskeletal rearrangements associated with cell motility and phagocytosis. Kynurenine administration resulted in several expression level changes in proteins associated with heat shock protein 90 (HSP90), a chaperone for the aryl-hydrocarbon receptor (AHR), which is the primary kynurenine metabolite receptor. We propose that cells with high levels of Quin are those that are currently releasing kynurenine pathway metabolites as well as accumulating Quin for sustained NAD+ synthesis from tryptophan. Further, the kynurenine pathway may be linked to the regulation of cell motility in immune and cancer cells.